SHIDIAN AND CHINESE PATH TO MODERNIZATION - Han , Junyao (Journal of Oriental Studies, 2024)
Different from Policy Experimentation in the Western context, the ShiDian is a "homegrown" Chinese style governance strategy and methodology tool, which frequently appears in the process of the CPC leading the Chinese people to promote and expand Chinese path to modernization. In view of this, this paper will comprehensively sort out the practice of ShiDian to promote Chinese path to modernization, and explain the internal logic of ShiDians and Chinese path to modernization. Firstly, this article analyzes the uniqueness of the ShiDian, which includes strong leadership mechanisms, non-controversial decision-making mechanisms, and innovative mechanisms for central and local cooperation. Second, this paper explains the advantages of the ShiDian in promoting Chinese path to modernization: correctly handling the important relationship between top-level design and practical exploration, effectively reducing the predictable and unpredictable exploration risks, and successfully resolving the resistance to the implementation of reform and innovation. Third, this paper discusses the ShiDian, how to promote Chinese path to modernization in different historical periods, and summarizes its achievements and experience.Fourth, this paper proposes countermeasures and suggestions for the new journey to continue to promote Chinese path to modernization through ShiDian from the aspects of political party leadership, high-quality development, spiritual strength, and the sense of integrity and innovation. Key words: CPC, ShiDian, Chinese path to modernization, Chinese characteristics, The great rejuvenation of the Chinese nation